Some features of the over-taxation of Ireland - Synnott, Nicholas J. (Statistical and Social Inquiry Society of Ireland, 1897)
In this paper, out of the wide ground covered by the recent investigation, I have chosen a very small field. I shall leave untouched the construction and effect of the Act of Union; the immense question as to the relative wealth of the two countries and the still more intricate problems that arise as to the incidence of taxation. I doubt whether on all these heads, there being so much of pure speculation mixed up with matters of fact, considerations such as these will turn the balance of opinion. Speculations as to what would have been Ireland's financial position had her parliaments and exchequers been separate; had her contributions to military and naval expenditure been voluntary; how she would have fared in her agriculture or commerce with a separate parliament and a system of bounties and custom duties; as to whether taxation if indirect, and therefore voluntary, is to be taken into account; and how far taxation of luxuries is a burden on the consumer, however ingenious, will be always too shadowy to persuade the British taxpayer at any rate that he has driven an unfair bargain or violated a fair one.
Read Thursday, 14th January, 1897.
Keywords: Taxation; Wealth, Ireland; 314.15